Costa Rica : Technical Assistance Report. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission to assist Costa Rica in delivering sound financial sector reform in support of financial stability. It was found that despite progress, the financial stability framework in Costa Rica is not well prepared to handle a potential systemic financial crisis without seriously compromising fiscal resources. Supervision of the financial sector is becoming risk-based and intensive, but it lacks key legal powers, tools, and responsibilities for the effective oversight of institutions and markets. Serious vulnerabilities in the pension sector, the secondary markets, and financial-crisis safety nets need urgent attention.